Reaching Out for Food: How Food Incentives Modulate Peripersonal Space Perception - Matias Bertonatti; Mathias Weymar; Werner Sommer; Martin H. Fischer (Journal of Cognition, 2021)
Two experiments were conducted to determine, first, whether food items influence participants’ estimations of the size of their subjective peripersonal space. It was of particular interest whether this representation is influenced by satiated/hungry states and is differentially affected by valence and calorie content of depicted stimuli. Second, event-related brain potentials (ERPs) were used, in order to obtain information about the time course of the observed effects and how they depend on the spatial location of the food pictures. For that purpose, participants had to decide whether food items shown at various distances along a horizontal plane in front of them, were reachable or not. In Experiment 1, when participants were hungry, they perceived an increase of their peripersonal space modulated by high-calorie items which were experienced as being more reachable than low-calorie items. In Experiment 2, the reachability findings were replicated and early and late components of ERPs showed an attentional enhancement in far space for food items when participants were hungry. These findings suggest that participants’ subjective peripersonal space increased while being hungry, especially for high-calorie contents. Attention also seems to be oriented more strongly to far space items due to their expected incentive-related salience, expanding the subjective representation of peripersonal space.